On the taxonomy of the jumping spider genus Matinta Ruiz & Maddison, 2019, with a taxonomic revision of the vicana species-group (Araneae: Salticidae: Amycini) - Matos, Tainá D.s.; Ruiz, Gustavo R.s. (Zootaxa, 2023)
The male of Matinta opiparis (Simon, 1900) is redescribed based on fresh material, and the female is described for the first time. Matinta tatianae sp. nov. (male) is described from Acre and Pará, Brazil. The vicana species-group of Matinta is revised, as follows: the males of M. silvae (Crane, 1943), M. fonsecai (Soares & Camargo, 1948), and M. vicana (Simon, 1900), and the female of M. silvae are redescribed based on fresh material. Three new species of the group are described: Matinta maddisoni sp. nov. from Morona Santiago, Ecuador (♂♀); Matinta pereirae sp. nov. from Amazonas, Brazil (♂); and Matinta aragog sp. nov. from French Guiana (♂). Detailed description of cheliceral dentition is given and commented. We conclude that the complex dentition within Amycini should be revised and more carefully studied.